CoSe2 nanoparticles embedded defective carbon nanotubes derived from MOFs as efficient electrocatalyst for hydrogen evolution reaction. (October 2016) - Zhou, Weijia; Lu, Jia; Zhou, Kai; Yang, Linjing; Ke, Yunting; Tang, Zhenghua; Chen, Shaowei
Abstract: Development of electrocatalysts for hydrogen evolution reaction (HER) with low overpotential and robust stability remained as one of the most serious challenges for energy conversion. In this work, CoSe2 nanoparticles embedded in defective carbon nanotubes (CoSe2 @DC) was synthesized by a carbonization-oxidation-selenylation procedure of Co-based metal-organic frameworks (MOFs). The pre-oxidation treatment was a crucial step in introducing an increasing number of defects into carbon nanotubes, which promoted the reaction between Co@carbon and selenium and led to the enhanced HER performance. The as-prepared CoSe2 @DC exhibited excellent HER catalytic reactivity with a low onset potential of −40 mV vs. RHE, a small Tafel slope of 82 mV dec −1 as well as a high current density with robust catalytic stability in 0.5 M H2 SO4 . This work may provide a generic methodology for rational design and fabrication of the partially encased core-shell structure derived from MOFs as efficient HER electrocatalysts. Graphical abstract: Highlights: CoSe2 embedded defective carbon nanotube via carbonization-oxidation-selenylation. The pre-oxidation as the crucial step introduced defects into carbon nanotubes. CoSe2 partially embedded defective carbon nanotubes can expose more active sites.